2014
DOI: 10.1089/chi.2014.0057
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Motivational Interviewing with a Nutrition and Physical Activity Assessment and Counseling Tool in Pediatric Clinical Practice: A Pilot Study

Abstract: The FNPA assessment with an MI-based counseling tool shows promise as an approach to identify and address obesigenic behaviors during pediatric well-child visits. It has the potential to improve provider efficacy in obesity prevention and also influence patient health behaviors, which can possibly impact childhood excessive weight gain. After refinement, this practice intervention will be used in a larger trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 40 publications
1
56
1
Order By: Relevance
“…11 A unique advantage of our enhanced SBMIS+ approach is the incorporation of the evidence-based online FNPA tool (www.myfnpa.org) designed to provide actionable information to assist parents in evaluating practices and home environments that could be targeted to help reduce their child's risk of obesity. 20 Longitudinal analyses have supported the predictive utility for identifying children who are at risk of becoming obese 21 and other studies have demonstrated associations with parenting style, 27 as well as effective links to provider counseling, 28 and clinical outcomes. 29 In this study, we observed that parents found greater utility in the SBMIS reports when provided with access to the FNPA assessment and the associated feedback, and educational links.…”
Section: Discussionmentioning
confidence: 95%
“…11 A unique advantage of our enhanced SBMIS+ approach is the incorporation of the evidence-based online FNPA tool (www.myfnpa.org) designed to provide actionable information to assist parents in evaluating practices and home environments that could be targeted to help reduce their child's risk of obesity. 20 Longitudinal analyses have supported the predictive utility for identifying children who are at risk of becoming obese 21 and other studies have demonstrated associations with parenting style, 27 as well as effective links to provider counseling, 28 and clinical outcomes. 29 In this study, we observed that parents found greater utility in the SBMIS reports when provided with access to the FNPA assessment and the associated feedback, and educational links.…”
Section: Discussionmentioning
confidence: 95%
“…The FNPA survey has been used in a number of studies and populations [22,23,24,25,26,27,28], including as a clinical screening tool to facilitate counseling and early intervention [27]. Previous research has supported both the construct [21] and predictive validity [22] of the FNPA in young children; however, it has not been examined in older youth.…”
Section: Introductionmentioning
confidence: 99%
“…Both FNPA and Healthy Kids risk assessments offer potential value to clinicians to involve parents in selfassessing risk using validated tools. This study did not evaluate parent experience or behaviour change following FNPA risk assessment; however, promising results have been observed in earlier studies (15,16). Enhancing BMI screening with FNPA risk assessment at routine WCVs was beneficial for children aged 2-9 and 2-5 overall, specifically those with normal weight at baseline, compared with children whose parents did not complete FNPA at baseline.…”
Section: Discussionmentioning
confidence: 84%
“…Both FNPA and Healthy Kids risk assessments offer potential value to clinicians to involve parents in self‐assessing risk using validated tools. This study did not evaluate parent experience or behaviour change following FNPA risk assessment; however, promising results have been observed in earlier studies .…”
Section: Discussionmentioning
confidence: 95%